Médecins sans frontières and the limitations of humanitarian aid: (filling a gap) - Costa, João Miguel Gomes de Almeida Gama (2021)
In 2015 the increasing number of people looking for shelter in Europe was portrayed as a “refugee crisis”. Due to a lack of response from European Union (EU) state-members, hundreds of humanitarian organizations were called to provide emergency aid to millions of refugees. This dissertation explores this crisis through the lens of one humanitarian organization in the Greek island of Lesvos, to understand their role and limitations in the attempt to “fill a gap” created by elected governments. Médecins Sans Frontières (MSF) was chosen not only because of its long history of humanitarian work, but also because of its critical position in the European response to the “refugee crisis”. By giving a voice to frontline health workers and asylum seekers, this dissertation addresses the most challenging years in Lesvos – 2019 to 2021, a period marked by the destruction of the largest refugee camp in Europe, Moria. Exploring MSF action during this period of the European “refugee crisis”, it is argued that the humanitarian organization has taken a side, the side of asylum seekers arriving, humanitarian actors have chosen the role of “active witnesses” instead of “merely spectators” (Terry, 2000, p.4) in a “non- neutral” way to answer to the limitations of humanitarian aid. With a constant call for political responsibility MSF refuses to be confined to a role and to exonerate states from their responsibilities. Instead of just “filling a gap”, the organization is open to challenge the role of the European Union (EU) in receiving refugees at its doorstep.